Co-occurrence of 3 different resistance plasmids in a multi-drug resistant Cronobacter sakazakii isolate causing neonatal infections. Issue 1 (1st January 2018) - Shi, Lining; Liang, Quanhui; Zhan, Zhe; Feng, Jiao; Zhao, Yachao; Chen, Yong; Huang, Mei; Tong, Yigang; Wu, Weili; Chen, Weijun; Li, Xiaojun; Yin, Zhe; et al.
ABSTRACT: Cronobacter sakazakii 505108 was isolated from a sputum specimen of a neonate with severe pneumonia. C. sakazakii 505108 co-harbors 3 resistance plasmids of the IncHI2, IncX3, and IncFIB incomparability groups, respectively. These 3 plasmids have acquired several accessory modules, which carry an extremely large number of resistance genes, especially including those involved in resistance to carbapenems, aminoglycoside, tetracyclines, and phenicols and sulphonamide/trimethoprim. These plasmid-borne antibiotic resistance genes were associated with insertion sequences, integrons, and transposons, indicating that the assembly and mobilization of the corresponding accessory modules with complex chimera structures are facilitated by transposition and/or homologous recombination. This is the first report of fully sequence plasmids in clinical Cronobacter, which provides a deeper insight into plasmid-mediated multi-drug resistance in Cronobacter from hospital settings.